Hollowed out Heartland, USA: How capital sacrificed communities and paved the way for authoritarian populism. (February 2021) - Edelman, Marc
Abstract: Communities prosper when they are able to appropriate the wealth they produce and their institutions make peoples' lives meaningful. They wither when the institutions that permit this weaken or vanish. Sacrifice zones — abandoned, economically shattered places, with growing social and health problems — are spreading in historically white rural areas and small towns across the United States. Rural decline, rooted in economic restructuring and financialization, causes severe stress, exacerbates racial resentment, and creates a breeding ground for regressive authoritarian politics. A multidimensional approach must analytically connect long-term and recent trends affecting economy and livelihoods, institutions, health, and community life. The "racial resentment" and "economic distress" explanations for authoritarian populism are inextricably connected. Since the 1980s, and in intensified form after the 2008 financial crisis, capital has systematically undermined the institutions — mutually-owned banks, credit unions, mom-and-pop businesses, family farms — that fostered reinvestment of locally-produced wealth, especially but not only in rural areas. While many Trump voters were affluent suburbanites, another important sector of supporters consists of downwardly mobile inhabitants of zones where financialization and austerity destroyed the institutions that earlier allowed people to appropriate the wealth that they produced and where the social safety net, always fragile, is increasingly in tatters. The United States now has a poor and near-poor majority. Scholars and the media have underestimated the human toll of this crisis and the interconnectedness of the multiple processes of social decomposition affecting rural zones. Highlights: Racism and economic distress factors in Trump's rise are inextricably connected. USA has a poor and near-poor majority that earns below the minimum survival budget. Severe economic distress increases receptivity to authoritarian populist rhetoric. Outside investors targeted mutual banks, coöps, businesses, newspapers and housing. Communities can no longer maintain tax bases or appropriate the wealth they produce.